Host range and pathogenicity of erwinia chrysanthemi, a causal pathogen of heart rot disease of pineapple / Radziah Abd Razak - Abd Razak, Radziah (Faculty of Plantation and Agrotechnology, 2018)
This study was specifically carried out to identify host range and pathogenicity of Erwinia chrysanthemi, a causal pathogen of heart rot disease of pineapple. The infected pineapple plant showing the symptoms of water-soaked lesions on the basal parts of the leaves in the centre of the whorl, blisters. Meanwhile, infection on pineapple fruits known as a fruit collapse disease with symptoms of exudes juice and unusual odour. Based on previous reports of soft rot diseases caused by Erwinia spp., several commercial fruits in Malaysia that have been identified as potential hosts were selected for a pathogenicity test. The pathogenicity test was conducted onto healthy detached fruits of pineapple, banana, papaya, corn, jackfruit, honeydew, starfruit, mango, dragon fruit, and guava. Each selected fruit was dedicated into three treatments which were artificial inoculated with 8 mm in diameter inoculum discs of pathogen on (i) unwounded fruit skin area, (ii) wounded fruit skin area, and (iii) control (nutrient agar discs without pathogen). A 48 hrs-old culture of E. chrysanthemi grown on nutrient agar was used as source of disease inoculum. All treatments were replicated with six fruits and incubated at 28oC in the moist chambers for 7 days. The experimental results indicated that, among these fruits, only pineapple, banana, and dragon fruit were infected by the pathogen. The remaining fruits did not show any disease incidence and remained as asymptomatic fruits similar as in the control treatment. Besides pineapple, it showed that banana and dragon fruit could become alternative hosts to E. chrysanthemi .Therefore, these crops should be considered before intercropped with pineapple plant. The remaining fruits that did not infected by the pathogen could be used as intercropping plants in the pineapple cultivation without worry on the disease infection and spread.